Reconstruction of porous electrodes by FIB/SEM for detailed microstructure modeling - Joos, Jochen; Carraro, Thomas (Journal of power sources, 2011)
Polarization losses within electrodes of solid oxide fuel cells (SOFCs) are determined both by material composition and microstructure. Improvement in performance can be supported by a detailed characterization and modeling of the electrode microstructure. Focused ion beam (FIB) and scanning electron microscopy (SEM) combined with image processing have already proven potential for the reconstruction of porous electrodes. In this contribution the serialized reconstruction procedure of a high-performance, mixed ionic-electronic conducting La0.58Sr0.4Co0.2Fe0.8O3−δ (LSCF)-cathode will be illustrated in detail. Based on corrected reconstruction data sets and by the evaluation of qualified algorithms discriminating between porosity and electrode material, a sensitivity analysis of the grayscale threshold value on the essential parameters (i) surface area, (ii) volume/porosity fraction and (iii) tortuosity is performed.